Math makers the lives and works of 50 famous mathematicians - Posamentier, Alfred S. (Prometheus Books, 2020)
"Two veteran math educators concisely profile leading mathematicians throughout history highlighting their often unusual personalities and lives while giving average readers insights into the importance of their mathematical discoveries."--